Explosive Leg Power and Its Relationship with Start and Turn Times in the 50-Meter Butterfly Swimming Performance of Youth Swimmers - Zain Al-Abidin Ali Raji Khudhair (Journal of Education and Sport Science, 2026)
Objectives: This study aimed to determine the relationship between explosive leg power and start and turn performance in youth 50-meter butterfly swimmers. Materials and Methods: This study used a descriptive correlational design. The sample consisted of 10 youth swimmers aged 15–18 years from North Gas Sports Club. Explosive leg power was measured using the standing vertical jump test, start time was measured from the starting signal to the 15-meter mark, and turn time was measured over a 10-meter distance after wall contact. Data were analyzed using mean, standard deviation, skewness, Pearson correlation, and t-test through SPSS version 26. Results: The findings showed that the data were normally distributed. Explosive leg power had a significant negative correlation with 50-meter butterfly performance time (r = -0.86, p = 0.002), start time (r = -0.82, p = 0.004), and turn time (r = -0.79, p = 0.006). Start time also showed a strong positive correlation with total performance time (r = 0.89, p = 0.001), while turn time was significantly correlated with total performance time (r = 0.81, p = 0.006). Conclusions: Explosive leg power is an important physical factor associated with faster starts, more efficient turns, and better 50-meter butterfly performance among youth swimmers. Coaches should emphasize lower-limb explosive power training and technical start-turn practice in sprint butterfly preparation.